Penggunaan mahkota dari gigi alami yang fraktur servikal sebagai pontik Using crown of natural tooth as a pontic on a tooth with cervical fracture - Syamsiah Syam (Journal of Dentomaxillofacial Science, 2012)
Replacement of missing anterior teeth can cause many problems, especially aesthetic. Immediate replacement of theanterior teeth can prevent psychological and social disruption to patients. This article explain the use of natural toothcrowns as a pontic following a cervical fracture using fiber reinforced material as post and to bond the natural toothcrown with adjacent teeth. The use of a natural tooth crown result excellent esthetic, efficient, and the procedure ismore economic